Applying systems ergonomics methods in sport: A systematic review - Hulme, A.; Thompson, J.; Plant, K. L.; Read, G. J. M.; Mclean, S.; Clacy, A.; Salmon, P. M. (Applied Ergonomics, 2018)
There is a growing body of systems ergonomics research in the context of sports performance and injury management. Systems ergonomics methods in sport attempt to consider the performance, health, and safety of the individual athlete in context with the wider settings that surround them. This systematic review reports on the purpose, contexts, outcomes, and study quality of the identified sports systems ergonomics applications. Further systems ergonomics applications in sport are required to better understand the full range of factors underpinning sports performance and injury management.